Read & think Italian - Think Italian magazine (New York McGraw-Hill, 2022)
Read & Think Italian contains more than 115 fascinating articles that reveal the enchanting diversity of Italian culture. Written in Italian, these readings provide insight into many aspects of Italian-speaking life and its traditions, from Lake Como glamor to a Sicilian flower festival, and from Vespa culture in Rome to the development of new customs around the Italian dining Table.

Within each article, new vocabulary is presented in boldface, with translations in the margins. This allows you to learn the meaning of any unfamiliar words immediately, without the burden of looking them up in a dictionary. And in the accompanying streaming audio recordings, native speakers read aloud 45 of the articles contained in the book, so you will not see how the language is written but also hear how it sounds in everyday conversation." -- Back cover.
Cultura -- Viaggi -- Tradizione -- Celebrazione -- Biografia -- Costume -- Le Arti -- Storia -- Geografia -- Gastronomia.
"Audio recordings for select readings (see page 239 for full list) and flashcards for all vocabulary lists are available to support your study of this book. Go to www.mhlanguagelab.com to access the online version of this application. Also available for iPhone, iPad, and Android devices. Search "McGraw Hill Language Lab" in the iTunes app store or Google Play App store for Android." --Verso t.p.
Keywords: Italian language -- English. -- Textbooks for foreign speakers; Italian language -- Grammar; Italian language -- Self-instruction.